Effect of arbuscular mycorrhizal fungi on growth of cinchona (Cinchona ledgeriana Moens) shoot cutting Cib5 and QRC clones - Agung Budi Laksono; Intan Ratna Dewi; Cucu Suherman; Joko Santoso (Research Institute for Tea and Cinchona, 2013)
AbstractThe purposes of this study were to observe the effect of interaction between arbuscular mycorrhizal fungi (AMF) and shoot cutting of quinine clones at nursery phase of quinine (Cinchona ledgeriana Moens) and to obtain the combination dosage AMF with the best Cinchona clone. The experiment began from March until June 2013 at Research Institute for Tea and Cinchona, Gambung, Bandung, West Java, on altitude 1.250 meters above sea level, type of soil Andisol with acidity 6,28 and type of climate B based on Schmidt and Fergusson (1951). This experiment used split plot as an experimental design with two factors and four replications. The main plot factor is Cinchona clones with two levels Cibeureum 5 (Cib5) and Quinine Research Center (QRC). The subplot is dosage of AMF with four levels, they are 0 g/shoot cutting, 5 g/shoot cutting, 10 g/shoot cutting, 15 g/shoot cutting. The result showed that there is no interaction between two clones Cib5 and QRC with the four dosages AMF to all measured variable. The AMF with 15 g/shoot cutting treatment showed the best effect to the percentage of AMF infection, root volume, and root length and significant for both two clones compare with lower AMF dosage.